Neoplasia, growth and growth hormone treatment : a reference guide - Brämswig, Jürgen, H. N; Hintz, Raymond L; Preece, M. A; Blum, Werner F; Chipman, John (TMG Healthcare Communications, 2004)
A reference guide that focuses on neoplastic diseases in childhood, cell growth and on growth hormone therapy. Intended for professional public.
Lilly genesis : next step for growth
Keywords: Cell Growth Processes; lékařská onkologie; Neoplasms; endokrinologie; Child; onkologie; dítě; Growth Disorders; genetika, lékařská genetika; poruchy růstu; Genetics, Medical; Hormone Replacement Therapy; Human Growth Hormone; hormonální substituční terapie; lékařská genetika; nádory; lidský růstový hormon; buňky - růstové procesy; Medical Oncology